Outcome of perineal wound following incision and drainage of perianal abscess - Akhanda, Muhammad T. A.; Ansary, Janifa; Khan, M. Shamsuddoha; Zaman, Fahmid U.; Ahmed, Farhad U.; Rahman, M. Zilanur; Bhuiyan, M. Masud Rana (International Surgery Journal, 2025)
Background: Perianal abscess is a benign but common clinical condition that may cause substantial discomfort to the suffering patients and carries significant burden on healthcare services. The aim of this study was to investigate the outcome of perineal wound following incision and drainage of perianal abscess. Methods: This prospective observational study was conducted in Department of Surgery, Shaheed Suhrawardy Medical College Hospital, Sher-E-Bangla Nagar, Dhaka, Bangladesh from 01 July 2019 to 30 June 2020. All the patients who were admitted to surgery department for incision and drainage of perianal abscess during this study period fulfilling the inclusion criteria were enrolled in the study. Results: A total number of 220 respondents were included in the current study. Anal pain and perianal swelling were the commonest symptoms (95.0%) of the study population. Majority of patients underwent incision and drainage (65%). Escherichia coli (n=25) was the commonest organism found in intra operative pus culture (25%). 11 (5%) patients had abscess recurrence and fecal incontinence. Besides, 20% patients (n=44) developed perianal fistula or sinus after 2 months of follow-up. Multivariate analysis showed diabetes mellitus (OR-2.17 955 CI: 2.11-2.23, p=0.001) poor anal hygiene (OR-1.36, 95% CI:1.31-1.42, p=0.001), absent Pre-operative pelvic MRI or EAS (OR-1.42, 95% CI: 1.38-1.51, p=0.001) and delayed presentation (OR-1.61, 95% CI:1.54-1.72, p=0.002) were independent predictors of recurrence of abscess and sinus/fistula formation. Conclusion: Further, large scale multicentric study is needed that may help to find and to compare the outcome of surgery as well as to evaluate the generalizability and applicability of the findings of this study.